Effect of bovine ovarian status on superovulation - Son, Hoang Nghia; Hanh, Nguyen Van; Huu, Quan Xuan; Chau, Le Thi (Academia Journal of Biology, 2013)
The goal of this study is using ultrasonic observations to evaluate effects of cow ovary status on superovulation results. The total of 30 dairy HF cows with high genetic productivity was ultrasonic screened for ovarian status, in which 15 ones without corpora lutea were chosen for superovulation. The cows with cystic ovaries having many follicles less than 6 mm were treated with FSH (Group 1) and PMSG (Group 2), whereas a group of cows with follicles larger than 6 mm was treated with FSH (Group 3). It is shown that Groups 1 had more embryos recovered than Group 3 (13.00 ± 3.22 and 6.60 ± 4.22, respectively) (P < 0.05). In Group treated by FSH (Group 1 and 3), the embryos collected higher quality than groups treated by PMSG (Group 2) (13.00 ± 3.22 and 8.80 ± 2.04 for group 1 & 3 and group 2, respectively). These results indicate that ultrasonic screening prior to superovulation might help predict the response of cow ovary. Superovulation using FSH is the most effective in cows with only small follicles.